INDICATORS OF ADAPTIVE IMMUNITY TO OPPORTUNISTIC BACTERIA IN NEWBORNS - An. A. Savisko; M. P. Kostinov; G. G. Harseeva; A. A. Savisko; A. D. Shmitko; N. E. Yastrebova; I. V. Podgorniy (Медицинский вестник Юга России, 2015)
Purpose: to evaluate the performance of transplacental adaptive immunity to opportunistic bacteria in newborns.Materials and Мethods: the study involved 682 newborn baby born to women 18-44 years old with various infectious anamnesis: weighed down (I group) and favorable infectious anamnesis (II group). Material for research is umbilical cord blood in that by linked immunosorbent analysis were determined IgG-antibody to opportunistic bacteria: S.aureus, S.epidermidis, S.pneumoniae, P.aerugonosa, E.coli, P.vulgaris, H.influenzae and K.pneumoniae.Results: it is set that a range of mean values of antibodies to оpportunistic bacteria was 36,5-60,6 conventional units at all 682 inspected. Thus, for the children of I of group their range hesitated within the limits of 41,3-57,2 conventional units, in II to the group - 50,3-64,7 conventional units. Lower values detected antibodies only to two оpportunisticbacteria -S. pneumoniae and H. influenzae in children in I group as compared to group II infants. And their level was lower in the umbilical cord blood of newborns born to women over the age of 25-30 years.Summary: the presence of infectious and inflammatory diseases in women during pregnancy, especially older than 25 years can be considered as a risk factor. This fact substantiates the need for the complex medical-diagnostic and preventive measures for the prevention of controlled infectious diseases caused by оpportunistic bacteria in the future in children.